CT Coronary Angiography Studies After a Mean Follow-up of 3.8 Years in Children With Kawasaki Disease and Spontaneous Defervescence - Dusad, Santosh; Singhal, Manphool; Pilania, Rakesh Kumar; Suri, Deepti; Singh, Surjit (Frontiers in Pediatrics, 2020)
Background: There is paucity of literature on follow-up of children with Kawasaki disease (KD) who have spontaneous defervescence during the acute stage and do not receive intravenous immunoglobulin. We report herein the role of computed tomography coronary angiography (CTCA) as an imaging modality in such situations. Methods: This prospective observational study was carried out during the period January 2016 - June 2017. Children underwent CTCA on 128-slice Dual Source CT (DSCT) scanner (Somatom Definition Flash, Siemens; Germany), and 2D-echocardiography on the same day. Results: Mean age at time of diagnosis was 6.52±3.13 years; range 2-14 years. Mean age at time of study was 11.03±5.10 years; range 3.75 - 23.30 years. Mean interval between diagnosis of KD and time of present study was 3.84±2.27 years. None of the patients showed any coronary artery abnormalities on either 2D-echocardiography or CTCA. While assessment of proximal segments of left main coronary artery, proximal right coronary artery, and left anterior descending artery was comparable on both 2D-echocardiography and CTCA, left circumflex artery and distal right coronary artery could be clearly visualized only on CTCA. Conclusion: In our experience, patients with KD who have spontaneous defervescence during the acute stage and do not receive IVIg may not have significant long-term coronary sequelae. CTCA is a useful imaging modality for delineation of coronary artery in patients with KD on long term follow-up especially in older children with thick chest walls and poor acoustic windows. Keywords: Kawasaki disease; Spontaneous defervescence; Dual Source computed tomography coronary angiography; Coronary artery abnormalities; 2D-echocardiography